2018
DOI: 10.2319/010418-4.1
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric comparison of adult anterior open bite treatment using clear aligners and fixed appliances

Abstract: Objectives: To compare fixed appliances and clear aligner therapy in correcting anterior open bite and in controlling the vertical dimension in adult patients with hyperdivergent skeletal patterns. Materials and Methods: In this retrospective study, two treatment groups of adult (≥18 years old) hyperdivergent patients (mandibular plane angles of ≥38°) with anterior open bites were included: 17 fixed appliance patients and 36 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
0
18

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 24 publications
5
55
0
18
Order By: Relevance
“…The average initial open bite for our patients at T0 was – 1.21 ± 1.15 mm. This pre-treatment severity was similar to the study by Khosravi et al [ 6 ] which had an initial open bite of – 1.1 mm, but less than those described by Moshiri et al [ 7 ] and Garnett et al [ 8 ]. Our results show that the average overbite change during treatment was 3.27 ± 1.09 mm.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The average initial open bite for our patients at T0 was – 1.21 ± 1.15 mm. This pre-treatment severity was similar to the study by Khosravi et al [ 6 ] which had an initial open bite of – 1.1 mm, but less than those described by Moshiri et al [ 7 ] and Garnett et al [ 8 ]. Our results show that the average overbite change during treatment was 3.27 ± 1.09 mm.…”
Section: Discussionsupporting
confidence: 90%
“…The fixed appliance group included patients treated with extractions and TADs (Temporary Anchorage Devices), while the clear aligner group did not. The results did not show any significant differences in the treatment outcomes between the groups, suggesting that clear aligners might have the same efficacy at controlling the vertical dimension as fixed appliances with additional auxiliaries, such as TADs in hyperdivergent patients [ 8 ]. Based on this limited evidence, additional research is needed to better clarify the mechanism by which aligners are primarily used in open bite correction.…”
Section: Introductionmentioning
confidence: 99%
“…As regards the analysis of single movements, the literature agrees that rotation of cone-shaped teeth [4] and movements that require good root control [6] are those most difficult to obtain with aligners, while crown tipping and intrusion are the most predictable [7][8][9]. In contrast, the literature contains differing reports on the efficacy of aligners in achieving extrusion [10]. That being said, it is generally agreed that aligners are particularly efficient at resolving malocclusions of slight to moderate complexity in non-extraction cases due to their good capacity to expand, align and level the arches [5,11].…”
Section: Introductionmentioning
confidence: 99%
“…The first reported anterior cross bite case treated by serial clear aligners was in 2009 by Park and Kim [ 1 ] that showed serial clear aligners made in the laboratory were able to move teeth sequentially into normal occlusion. A recent study showed that clear aligners are as effective as fixed orthodontic appliances in correcting open bite cases [ 2 ]. Recent case reports showed that clear aligners could be successfully used to correct Class III malocclusion and open bite cases with or without surgery.…”
Section: Introductionmentioning
confidence: 99%